A Case for Adapting Channel Width in Wireless Networks - Chandra, Ranveer; Mahajan, Ratul; Moscibroda, Thomas; Raghavendra, Rayma; Bahl, Victor (SIGCOMM 2008: ACM SIGCOMM Conference on Applications, Technologies, Architectures, and Protocols for Computer Communications, Seattle, WA, 2008)
We study a fundamental yet under-explored facet in wireless communication – the width of the spectrum over which transmitters spread their signals, or the channel width. Through detailed measurements in controlled and live environments, and using only commodity 802.11 hardware, we first quantify the impact of channel width on throughput, range, and power consumption. Taken together, our findings make a strong case for wireless systems that adapt channel width. Such adaptation brings unique benefits. For instance, when the throughput required is low, moving to a narrower channel increases range and reduces power consumption; in fixed-width systems, these two quantities are always in conflict. We then present SampleWidth, a channel width adaptation algorithm for the base case of two communicating nodes. This algorithm is based on a simple search process that builds on top of existing techniques for adapting modulation. Per specified policy, it can maximize throughput or minimize power consumption. Evaluation using a prototype implementation shows that SampleWidth correctly identities the optimal width under a range of scenarios. In our experiments with mobility, it increases throughput by more than 60% compared to the best fixed-width configuration.